Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2741/1890
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of perinatal brain injury in the preterm infant

Abstract: Due to developmental immaturity of the central nervous system, effects of an adverse intrauterine environment and need for intensive care postnatally, preterm infants are at high risk of sustaining brain injury in the perinatal period. Infants who suffer brain injury in the perinatal period are at risk for long-term neurodevelopmental sequelae. Clinical and experimental data supports a significant role for inflammatory mediators in the pathophysiology of perinatal brain injury. Abnormalities in coagulation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 129 publications
3
42
0
9
Order By: Relevance
“…Other potential mechanisms involved in eliciting a differential response/recovery from hypoxic insult may include differences in VEGF expression and induction, 61 differences in BDNF expression level, induction, 62 and polymorphism 63 and polymorphisms in several cytokines and extracellular matrix components. 64,65 Thus, in this report we have documented significant differences in HIF-1␣ translation and responsiveness to SDF-1 in C57 and CD-1 NSCs (shaded aspects of the signaling pathways are illustrated in Figure 7). 48,50 -52 Specifically, C57 NSCs exhibit blunted HIF-1␣ translation in response to a reduced O 2 culture environment.…”
Section: Discussionsupporting
confidence: 52%
“…Other potential mechanisms involved in eliciting a differential response/recovery from hypoxic insult may include differences in VEGF expression and induction, 61 differences in BDNF expression level, induction, 62 and polymorphism 63 and polymorphisms in several cytokines and extracellular matrix components. 64,65 Thus, in this report we have documented significant differences in HIF-1␣ translation and responsiveness to SDF-1 in C57 and CD-1 NSCs (shaded aspects of the signaling pathways are illustrated in Figure 7). 48,50 -52 Specifically, C57 NSCs exhibit blunted HIF-1␣ translation in response to a reduced O 2 culture environment.…”
Section: Discussionsupporting
confidence: 52%
“…4 A recent study by Ko et al 12 revealed that polymorphism of the eNOS allele led to a statistically significant increase in risk of vasospasm after subarachnoid hemorrhage, specifically the CC genotype of the eNOS -786 polymorphism. 2 We have shown that this C allele is also linked to an increased risk of specific conditions of prematurity.…”
Section: 11mentioning
confidence: 94%
“…Furthermore, the effects of IVH can be devastating, including periventricular scarring, white matter gliosis, and free radical and cytokine generation, all of which produce secondary damage to the early developing brain. [1][2][3][4][5]7 Studies have shown that infants who suffer large IVH are associated with an increased rate of developing major disabilities. As many as 60% of infants with Grade IV IVH will have severe motor and/or cognitive handicaps.…”
mentioning
confidence: 99%
“…Sitokinler ile ilgili polimorfizmlerin pre ve perinatal beyin hasarını etkilediğine yönelik gün geçtikçe daha çok delil elde edilmektedir [31]. Bu polimorfizmler, proinflamatuar veya antiinflamatuar sitokinlerin salınımını etkileyen genetik farklılıklardır.…”
Section: Patofizyolojiunclassified